Virtual interactive interior walkthrough using unity3d - Yeap, Mei Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
Unity3D is known for being a game developing software instead one for interior or architectural design. The development of increasingly complex video games had increased the popularity of 3D environments. This study aims to reexplore the utilizing this software to explore the ability of Unity 3D in creating virtual interactive showroom. It also aims to provide an interactive walkthrough where users can experience and freely explore the virtual environment. User experience and minor technical performance are analysed to evaluate the [mal product of the virtual environment produced